Hubungan Kearifan Lokal dengan Ramah Sekolah bagi Siswa dan Guru di SMPN 11 Tanjung Pinang - Napsiah; Mia Rizki Anggrela; Indra Jaya; Muliwarman; Nur Izzati; Desi Rahmatina (Fakultas Ilmu Tarbiyah dan Keguruan, Institut Agama Islam Bakti Negara Tegal, 2025)
This study aims to analyze the relationship between local wisdom and school friendliness as perceived by students and teachers at SMPN 11 Tanjung Pinang. In the context of education, local wisdom which includes values such as mutual cooperation (gotong royong) and politeness as well as a school friendly environment, are considered crucial in shaping a positive learning ecosystem. This research employs a quantitative approach with a correlational design. The sample consisted of 172 respondents, including 14 teachers and 158 students. Data were collected using a closed ended questionnaire that had been tested for validity and reliability. The assumption tests revealed that the data were not normally distributed, but the variances between groups were homogeneous. Therefore, the Spearman Rank correlation was used to analyze the relationship between the variables. The findings show that both variables local wisdom (mean score = 86.59) and school friendliness (mean score = 44.10) were perceived at a relatively high level by respondents. The Spearman Rank correlation analysis indicated a very strong, positive, and significant relationship between local wisdom and school friendliness (rho = 0.786, p < 0.001). This suggests that the higher the internalization of local wisdom values, the more positive the perception of a friendly, safe, and supportive school environment. These results highlight the importance of preserving and integrating local wisdom as an effective strategy to create a more positive school climate.